The Effect of Repeated Advertising on Purchase Behavior Moderated by Consumer Trust - Burhan Rifuddin; Ilham; Sukran; Hamida; nurfadilah; Muh. Abdi Imam; Ahmad Nouruzzaman (Al-Kharaj: Journal of Islamic Economic and Business, 2026)
This study aims to analyze the effect of repeated advertising on purchase behavior with trust as an intervening and moderating variable. The study uses a quantitative approach through a survey of respondents, with data analysis using the Partial Least Squares–Structural Equation Modelling (PLS-SEM) method. The measurement model was evaluated through validity and reliability tests based on outer loading, composite reliability, and average variance extracted (AVE) values. The analysis results show that repeated advertising has a positive and significant effect on purchase behavior and trust. In addition, trust also has a positive and significant effect on purchase behavior. However, the moderation test results show that trust does not moderate the relationship between repeated advertising and purchase behavior. The R-square value shows that repeated advertising explains 37.3% of the variation in purchase behavior and 14.2% of the variation in trust. These findings confirm the important role of repeated advertising in shaping trust and directly encouraging consumer purchase behavior. This study provides theoretical and practical implications for the development of marketing communication strategies.